Evidence of a complex association between dose, pattern and timing of prenatal alcohol exposure and child behaviour problems. - O'Leary, C; Nassar, N; Zubrick, SR; Kurinczuk, J; Stanley, F; Bower, C (2010)
BACKGROUND: There is a lack of evidence regarding the effect of dose, pattern and timing of prenatal alcohol exposure and behaviour problems in children aged 2 years and older. METHODS: A 10% random sample of women delivering a live infant in Western Australia (1995-96) were invited to participate in an 8-year longitudinal survey (78% response rate n = 2224); 85% were followed-up at 2 years, 73% at 5 years and 61% at 8 years. Alcohol consumption was classified by combining the overall dose, dose per occasion and frequency to reflect realistic drinking patterns. Longitudinal analysis was conducted using generalized estimating equations (GEE) to investigate the association between child behaviour as measured by the Child Behaviour Checklist at 2, 5 and 8 years of age and prenatal alcohol exposure collected 3 months postpartum for each trimester separately, adjusting for a wide range of confounding factors. RESULTS: Low levels of prenatal alcohol were not associated with child behaviour problems. There were increased odds of internalizing behaviour problems following heavy alcohol exposure in the first trimester; anxiety/depression [adjusted odds ratio (aOR) 2.82; 95% confidence interval (CI) 1.07-7.43] and somatic complaints (aOR 2.74; 95% CI 1.47-5.12) and moderate levels of alcohol exposure increased the odds of anxiety/depression (aOR 2.24; 95% CI 1.16-4.34). CONCLUSIONS: Prenatal alcohol exposure at moderate and higher levels increased the odds of child behaviour problems with the dose, pattern and timing of exposure affecting the type of behaviour problems expressed. Larger studies with more power are needed to confirm these findings.